Activating transcription factor 3 SUMOylation is involved in angiotensin II-induced endothelial cell inflammation and dysfunction. (March 2016) - Zhang, Ze-Bei; Ruan, Cheng-Chao; Chen, Dong-Rui; Zhang, Ke; Yan, Chen; Gao, Ping-Jin
Abstract: Activating transcription factor 3 (ATF3) is an adaptive-response protein induced by various environmental stresses and is implicated in the pathogenesis of many disease states. However, the role of ATF3 SUMOylation in hypertension-induced vascular injury remains poorly understood. Here we investigated the function of ATF3 SUMOylation in vascular endothelial cells (ECs). The expression of ATF3 and small ubiquitin-like modifier 1 (SUMO1) was increased in angiotensin II (Ang II)-induced human umbilical vein endothelial cells (HUVECs). Microscopic analyses further revealed that the expression of ATF3 and SUMO1 is upregulated and colocalized in the endothelium of thoracic aortas from Ang II-induced hypertensive mice. However, Ang II-induced upregulation of ATF3 and SUMO1 in vitro and in vivo was blocked by Ang II type I receptor antagonist olmesartan. Moreover, Ang II induced ATF3 SUMOylation at lysine 42, which is SUMO1 dependent. ATF3 SUMOylation attenuated ATF3 ubiquitination and in turn promoted ATF3 protein stability. ATF3 or SUMO1 knockdown inhibited Ang II-induced expression of inflammatory molecules such as tumor necrosis factor (TNF)-α, interleukin (IL)-6 and IL-8. Wild type ATF3 but not ATF3-K42R (SUMOylation defective mutant) reduced the production of nitric oxide (NO), a key indicator of EC function. Consistently, ginkgolic acid, an inhibitor of SUMOylation, increased NO production in HUVECs and significantly improved vasodilatation of aorta from Ang II-induced hypertensive mice. Our findings demonstrated that ATF3 SUMOylation is involved in Ang II-induced EC inflammation and dysfunction in vitro and in vivo through inhibiting ATF3 ubiquitination and increasing ATF3 protein stability. Highlights: ATF3 SUMOylation increased in Ang II-induced endothelial cells in vitro and in vivo. SUMOylation enhanced ATF3 protein stability in endothelial cells. ATF3 SUMOylation contributed to Ang II-induced endothelial cell inflammation. ATF3 SUMOylation contributed to Ang II-induced endothelial cell dysfunction. SUMOylation inhibitor improved vasodilatation of Ang II-induced hypertensive mice.